Investigation of long term problems after obstetric epidural anaesthesia. Issue 6837 (16th May 1992) - MacArthur, C.; Lewis, M.; Knox, E. G.
Abstract : OBJECTIVE--To examine the association between obstetric epidural anaesthesia and subsequent long term problems. DESIGN--Postal questionnaire on health problems after childbirth linked to maternity case note data. SETTING--Maternity hospital in Birmingham. SUBJECTS--11701 women who delivered their most recent child during 1978-85 and who returned completed questionnaires. MAIN OUTCOME MEASURES--Frequencies of long term symptoms after childbirth. RESULTS--Compared with the 6935 women who did not have epidural anaesthesia the 4766 women who did more commonly experienced backache (903 (18.9%) with epidural v 731 (10.5%) without epidural), frequent headaches 220 (4.6%) v 199 (2.9%)), migraine (92 (1.9%) v 73 (1.1%)), neckache (116 (2.4%) v 112 (1.6%)), and tingling in hands or fingers (143 (3.0%) v 150 (2.2%)). The results could not be explained by correlated social or obstetric factors. The associations with head, neck, and hand symptoms were found only in women who reported backache. An excess of visual disturbances among women who had epidural anaesthesia (83 (1.7%) v 91 (1.3%)) was present only in association with migraine, but excess of dizziness or fainting (102 (2.1%) v 109 (1.6%)) was independent of other symptoms. 26 women had numbness or tingling in the lower back, buttocks, and leg, of whom 23 had had epidural anaesthesia. Of 34 women with spinal headache, nine (five after accidental dural puncture; four after spinal block) reported long term headaches. CONCLUSIONS--These associations may indicate a causal sequence, although this cannot be proved from this type of study. Randomised trials of epidural anaesthesia are required to determine whether causal relations exist.